Interplanetary Magnetic Field (IMF) control over the global structures of laboratory magnetosphere - Wei-Tsung Fu; Gung Yur; Chi-Kuang Chao; Hafiz-Ur Rahman (Terrestrial, Atmospheric and Oceanic Sciences, 2020)

(untitled)
Both east-west and north-south view images of magnetosphere for various interplanetary magnetic field (IMF) parameter have been investigated simultaneously in a laboratory experiment of the solar wind-magnetosphere coupling. An aurora is observed for both case of southward and northward IMF but the luminosity becomes stronger for southward IMF. The X type reconnections in the front and tail areas for southward IMF clearly shown in the magnetosphere images for higher IMF magnitude. The distances between the terrella and the front side and tail reconnection for southward IMF are increased as the magnitude of IMF decreases. A sector of discontinuity boundary which corresponds to the reconnection area is observed on the tail region of the north-south view magnetosphere when the IMF is southward. With northward IMF applied, a long narrow plasma beam jet in the magnetotail has been observed for the east-west view while a water drop shape of magnetotail is shown in the north-south view. Inserting the 20 degree terrella tilt, the study of modeling analysis is also processed for comparison with photograph of the experimental results in the laboratory simulation. The OpenGGCM model on CCMC overview of the global structure, the comparisons show that the model presented lower temperature in the magnetotail for the northward IMF. This corresponds to the weak and diffused tail in the laboratory simulation. For the southward IMF, the model presented higher temperature in the magnetotail, which corresponds to the more luminous tail region in the laboratory simulation. And the curvature of the magnetic lines due to the dipole tilt is qualitatively matched.